2018
DOI: 10.1371/journal.ppat.1006943
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of echovirus 11 in a chronically infected immunodeficient patient

Abstract: Deep sequencing was used to determine complete nucleotide sequences of echovirus 11 (EV11) strains isolated from a chronically infected patient with CVID as well as from cases of acute enterovirus infection. Phylogenetic analysis showed that EV11 strains that circulated in Israel in 1980-90s could be divided into four clades. EV11 strains isolated from a chronically infected individual belonged to one of the four clades and over a period of 4 years accumulated mutations at a relatively constant rate. Extrapola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The role of cytokines in echovirus pathogenesis in humans is not known. However, immunodeficient individuals, including adults, are more susceptible to echovirus infections, which often induces hepatitis [33][34][35][36]. In addition, analysis of mutations in the E11 genome induced by selective pressure in an immunodeficient individual who developed chronic infection revealed strikingly high sequence conservation in the 3C virally-encoded protease which often attenuates host cell innate immune signaling [36].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of cytokines in echovirus pathogenesis in humans is not known. However, immunodeficient individuals, including adults, are more susceptible to echovirus infections, which often induces hepatitis [33][34][35][36]. In addition, analysis of mutations in the E11 genome induced by selective pressure in an immunodeficient individual who developed chronic infection revealed strikingly high sequence conservation in the 3C virally-encoded protease which often attenuates host cell innate immune signaling [36].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…However, immunodeficient individuals, including adults, are more susceptible to echovirus infections, which often induces hepatitis [33][34][35][36]. In addition, analysis of mutations in the E11 genome induced by selective pressure in an immunodeficient individual who developed chronic infection revealed strikingly high sequence conservation in the 3C virally-encoded protease which often attenuates host cell innate immune signaling [36]. Our studies suggest that type I IFNs are the primary drivers of resistance to echovirus infections in the liver, which is supported by our RNASeq studies, in which low levels of the transcripts for type III IFNs were upregulated by infection.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…We next examined children with multiple EV-B infections (i.e., >1 positive sample) and asked if these are multiple positive stools for the same strain of one serotype, which would indicate a prolonged shedding period lasting more than 30 days. The definition of "same virus strain" within a serotype was set as a RNA sequence homology >98% (i.e., evolution rate of acquired mutations during chronic EV-B infection 12 ). The same EV-B serotype strain in more than one positive sample was observed in 11.8% (45/383) of cases and 6.5% (25/383) of controls.…”
mentioning
confidence: 99%
“…However, enterovirus infections can be particularly problematic in patients with a weakened immune system. Indeed, studies have shown that some enteroviruses can persist for years in the body and can be continually shed in faeces ( Laassri et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the persistence of EV-C104 in patients. However, poliovirus, one of the most well-studied group C enteroviruses, has been known to persist in the body for over 30 years ( Laassri et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%